2020
DOI: 10.1093/mnrasl/slaa066
|View full text |Cite
|
Sign up to set email alerts
|

Limiting the shock acceleration of cosmic ray protons in the ICM

Abstract: Observations of large-scale radio emissions prove the existence of shock accelerated cosmic ray electrons in galaxy clusters, while the lack of detected γ-rays limits the acceleration of cosmic ray protons in galaxy clusters. This challenges our understanding of how diffusive shock acceleration works. In this work, we couple the most updated recipes for shock acceleration in the intracluster medium to state-of-the-art magnetohydrodynamical simulations of massive galaxy clusters. Furthermore, we use passive tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 31 publications
3
38
0
Order By: Relevance
“…CRe are accelerated preferentially at quasi-perpendicular shocks and CRp at quasi-parallel shocks. Recent works by Wittor et al (2020) and Banfi, Vazza & Wittor (2020) used cosmological MHD simulations to show that indeed the predominance of quasi-perpendicular shocks in merger and accretion shocks might be enough to explain the absence of CRp. Therefore, in future work we will include the obliquity dependence in our acceleration efficiency, η.…”
Section: S U M M a Ry A N D C O N C L U S I O N Smentioning
confidence: 99%
“…CRe are accelerated preferentially at quasi-perpendicular shocks and CRp at quasi-parallel shocks. Recent works by Wittor et al (2020) and Banfi, Vazza & Wittor (2020) used cosmological MHD simulations to show that indeed the predominance of quasi-perpendicular shocks in merger and accretion shocks might be enough to explain the absence of CRp. Therefore, in future work we will include the obliquity dependence in our acceleration efficiency, η.…”
Section: S U M M a Ry A N D C O N C L U S I O N Smentioning
confidence: 99%
“…Yet, only a direct detection of a γ-ray signal associated with cosmic-ray protons in the ICM will allow to pin-point the exact shock acceleration mechanism. Though, estimates by Wittor et al (2020) showed that, even after ten more years of operation, the Fermi-LAT will most-likely not detect such a signal, see Fig. 5.…”
Section: Will There Be a Detection In The Future?mentioning
confidence: 98%
“…During the processes of hierarchical structure formation, galaxy clusters form through 1 Here, β is the plasma β that gives the ratio between gas pressure and magnetic pressure. Wittor et al (2020): the two panels show the expected γ-ray emission (color) of two simulated galaxy clusters at redshift z = 0. The underlying cosmic-ray model is the most restricted one, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations